Assessment of coke quality related to of effective permeability coefficient and anisotropy coefficient - Wałowski, Grzegorz (Fuel (Guildford), 2019)
•Assessment of anisotropy coefficient of coke.•Coke with an anisotropic gap-porous structure.•Measuring the gas permeability coefficient of coke.•Impact of the flow direction on the gas permeability of coke.•Hydrodynamics of the gas flow through coke. The assessment of process phenomena resulting from the hydrodynamics of gas flow through various kinds of coal chars may refer to a vast number of technological aspects pertaining to qualitative features of those materials. Those issues are subject to the assessment of the post-reaction gas movement in the conditions of the thermal processing of coal substances. In the case, an additional aspect of this assessment is also phenomena referring to the determination of the permeability of coal chars in the context of their application in other technological processes, e.g. coke in the metallurgical cycle. In the context of research upon the hydrodynamics of gas flow through porous materials an attempt was made to correlate the results of that research with the process issues resulting from the technological reasons for applying various kinds of coal chars. This correlation was referred to the assessment of the technological quality of coke referring to its features for the blast furnace technology. The basis for the assessment was the obtained results referring to the measurement of structural features of the analysed coal chars and the hydrodynamics resulting from their gas permeability.